First-charge instabilities of layered-layered lithium-ion-battery materials. Issue 37 (7th October 2015) - Croy, Jason R.; Iddir, Hakim; Gallagher, Kevin; Johnson, Christopher S.; Benedek, Roy; Balasubramanian, Mahalingam
<x xml:space="preserve">Abstract</x> Dynamical simulation at 1000 K shows the migration of oxygen ions in delithiated Li7/6−xNi1/4Mn7/12O2 (with x = 1) from oxygen layers (lower panel, at t = 0) to form O–O pairs (upper panel at t = 35 ps) thereby lowering the energy of charged cathode material.